2017
DOI: 10.1371/journal.pone.0180535
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-148a overexpression improves the early development of porcine somatic cell nuclear transfer embryos

Abstract: Incomplete epigenetic reprogramming of donor cell nuclei is one of the main contributors to the low efficiency of somatic cell nuclear transfer (SCNT). To improve the success of SCNT, somatic cell DNA methylation levels must be reduced to those levels found in totipotent embryonic cells. Recent studies have demonstrated that miR-148a can affect DNA methylation via DNMT1 modulation in various cancers. Therefore, the focus of this study was to examine the influence of miR-148a on DNA methylation in donor cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 35 publications
3
20
0
Order By: Relevance
“…However, miR-101-2 expression levels at the blastocyst stage showed no significant differences (P > 0.05). Wang et al (2017b) indicated using donor cells with miR-148a overexpression could upregulate its expression in cloned embryo, and similar results were found in another study, with miR-449b being selected (Wang et al, 2017a). These results are in line with our findings.…”
Section: Characterization Of Mir-101-2 Expression In Ivf and Scnt Embsupporting
confidence: 93%
“…However, miR-101-2 expression levels at the blastocyst stage showed no significant differences (P > 0.05). Wang et al (2017b) indicated using donor cells with miR-148a overexpression could upregulate its expression in cloned embryo, and similar results were found in another study, with miR-449b being selected (Wang et al, 2017a). These results are in line with our findings.…”
Section: Characterization Of Mir-101-2 Expression In Ivf and Scnt Embsupporting
confidence: 93%
“…Improvement of methylation reprogramming may be a useful approach for improving SCNT efficiency. A previous study demonstrated that overexpression of miR‐148a , which can affect DNA methylation via DNMT1 modulation, modifies epigenetic status of porcine SCNT embryos and enhances developmental potential . Gao et al .…”
Section: Discussionmentioning
confidence: 99%
“…Improvement of methylation reprogramming may be a useful approach for improving SCNT efficiency. A previous study demonstrated that overexpression of miR-148a, which can affect DNA methylation via DNMT1 modulation, modifies epigenetic status of porcine SCNT embryos and enhances developmental potential [63]. Gao et al successfully replaced Oct4 with Tet1 during induced pluripotent stem cell (iPSC) induction and revealed that changes in DNA 5mC modification and 5hmC modification perform important roles in remodeling genome-wide epigenetic states during reprogramming [17].…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al [131] employed tauroursodeoxycholic acid (TUDCA), an inhibitor of endoplasmic reticulum (ER) stress, and demonstrated that TUDCA can enhance the developmental potential of porcine SCNT embryos by attenuating ER stress and reducing apoptosis. Wang et al [132] demonstrated that administration of siRNA or microRNA-148a, both of which can suppress the function of DNA methyltransferase 1 (DNMT1) at a transcriptional level, is effective for enhancing the developmental potential of SCNT embryos. Furthermore, Matoba et al [133] succeeded in drastically increasing SCNT efficiency by cytoplasmic MI of mRNA coding for histone demethylase (Kdm4d) in mice.…”
Section: Scntmentioning
confidence: 99%